Analisis Design For Assembly (DFA) pada Prototipe Mesin Pemisah Sampah Material Ferromagnetik Dan Non Ferromagnetik - Arief, Dodi Sofyan; Abidin, Tekad Indra Pradana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Design for assembly is one of systems analysis to assembling components, simultaneously, throughout the products from beginning of process design. As result, obstacles to get assembly could be minimalizing before components production. DFA analysis will be obtaining the value of efficiency on assembly. Through this way, the efficiency value of machine prototype to separating waste, both, ferromagnetic and non-ferromagnetic materials can be achieved. Furthermore, efficiency value on assembly of prototype design is 14.22% at 548.47 seconds theoretically. The efficiency value of prototype after production and assembling process on actual condition is 11.83% at 658.88 seconds. The distinction from these efficiency values is caused by difficulty on assembly of the belt roller and sub assembly of base support on motor. As consequences, the time to get assembly will take more time on actual condition rather than theoretically.Keywords : Design For Assembly (DFA), Efisiency Assembly